Study of Ammonia Electro-oxidation on Pt-based Nano-catalysts Using Polarization Modulation IRRAS - Aligholizadeh Kahriz, Niloofar (Université d'Ottawa / University of Ottawa, 2020)
Ammonia electrochemical oxidation is a viable technology for power generation in fuel cells since ammonia is a versatile hydrogen carrier that possesses high energy density and hydrogen content with lower energy consumption compared to the other candidates. Pt is the most active catalyst toward ammonia oxidation reaction as shows in high activity and stability. In the present study, Pt nanoparticles (NPs) were synthesized in 4 different sizes (1.3 - 4.3 nm) dispersed on carbon support using the polyol method. The effect of particle size on the catalytic activity and reaction product distribution was evaluated. The correlation between nano-catalyst size and catalytic activity has been demonstrated in the research. Pt particle size of 1.3 nm yielded comparatively better activity although Pt 2.2 nm was more stable in addition to acceptable activity. Polarization modulation infrared reflection absorption spectroscopy (PM-IRRAS) was employed to analyze the formation of reaction species in real-time when the electrooxidation was occurring. Unlike regular infrared spectroscopy, PM-IRRAS enabled us to observe oxidation species on both catalyst-electrolyte interface and bulk of the solution. N-H containing species as well as nitro compounds and azide ions were identified at individual potentials on the surface of catalysts and in the bulk of electrolyte. Furthermore, Pt and Pt-based bimetallic NPs, including PtIr and PtRu, were prepared on engineered carbon support (ECS) provided for Pt group metals (PGM) in order to improve the catalyst dispersion. In the first evaluation step, the catalytic activity was tested by electrochemical measurements which indicated that incorporation of Ir enhanced the stability of the catalyst comparing to pure Pt. Besides the stability, the addition of second metal lowered the oxidation onset potential to more negative overpotential that was verified by PM-IRRAS. The resulting current density of catalysts in various concentrations of ammonia was assessed in alkaline solution. The overall upward trend in catalytic activity for PtIr and PtRu in contrast to Pt might be due to enhanced tolerance regarding N adsorbate atoms poisoning effect that occurred by the addition of Ir and Ru. The effect of carbon supports was evaluated by making a comparison between Pt/C ECS and Pt/C (commercial Vulcan XC-72) at approximately the same size around 4.5 nm and the same metal loading. Compared to untreated carbon, the substantially higher current density associated with Pt/C ECS demonstrates the effect of the support structure on the catalytic activity of Pt NPs towards ammonia electrooxidation. Improved dispersion and enhancement of the interaction between catalyst and electrolyte can be considered for a significant difference in corresponding current densities.
Keywords: Ammonia; Electro-oxidation; PM-IRRAS; Nano-catalyst; Nanoparticles; Particle size effect